2010
DOI: 10.3342/ceo.2010.3.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Neural Stem Cells in Anosmic Mice

Abstract: ObjectivesTreating olfactory dysfunction is a challenge for physicians. One of the therapeutic options could be transplantation of stem cells. In this study, neural stem cells were transplanted into anosmic mice.MethodsNeural stem cells were generated from the olfactory bulb of green fluorescent protein (GFP)-transgenic C57BL6 mice. Anosmia were induced by injection of intraperitoneal 3-methylindole. The neural stem cells were transplanted transnasally on the next day. The olfactory function was evaluated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Lee et al reported a significant improvement in anosmia after olfactory neuroepithelial stem cell transplantation in mice. 5 Nota et al found significant improvement in anosmia in their study group (anosmia-induced mice) after infiltration of basic fibroblast growth factor (bFGF). 6 Platelet-rich plasma treatment is a process in which a small amount of blood from a test subject is separated into its components by a special centrifugation process, and the resulting PRP is administered to the same subject via injection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lee et al reported a significant improvement in anosmia after olfactory neuroepithelial stem cell transplantation in mice. 5 Nota et al found significant improvement in anosmia in their study group (anosmia-induced mice) after infiltration of basic fibroblast growth factor (bFGF). 6 Platelet-rich plasma treatment is a process in which a small amount of blood from a test subject is separated into its components by a special centrifugation process, and the resulting PRP is administered to the same subject via injection.…”
Section: Discussionmentioning
confidence: 99%
“…If local growth factors or stem cells are applied to this region, they may trigger this potential. Lee et al reported a significant improvement in anosmia after olfactory neuroepithelial stem cell transplantation in mice . Nota et al found significant improvement in anosmia in their study group (anosmia‐induced mice) after infiltration of basic fibroblast growth factor (bFGF) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental neural anosmia has often been induced by administering various olfactotoxic agents, such as zinc sulfate, 12 3-MI, [13][14][15] and methimazole. 16 In this study, we used 3-MI to impair ORNs of the olfactory epithelium, although it also caused bronchiolar insult.…”
Section: Commentmentioning
confidence: 99%